Apologia miłości w Quo Vadis Henryka Sienkiewicza - Bielat, Andrzej (Studia Teologiczne Białystok Drohiczyn Łomża, 2023)
The article “Apology for love in Quo Vadis by Henryk Sienkiewicz” consists of three parts. In the first one, I show two Dominican theologians from first half of 20th century: Józef M. Bocheński OP and Jacek Woroniecki OP who in the novels by Henry Sienkiewicz found valuable loci theologici. In the second part, I present a literary work by a contemporary researcher of Sienkiewicz’s creativity prof. Ryszard Koziołek, in which, he confirms the biblical anthropology of the novel Quo Vadis. In the third part, I analize the text of the novel and show the repention of the main characters in their comprehension of love: Winicjusz moves on from pagan concept of possessing the beloved to Christian virtue; Ligia repents from the fear of carnality and spiritualism to the fullness of love expressed in the mistery of Incarnation.